Nomogram Based on Log Odds of Positive Lymph Nodes Predicting Cancer-Specific Survival in Patients With T3 and T4 Gallbladder Cancer After Radical Resection - Yuan, Chen; Tao, Qiaomeng; Wang, Jian; Wang, Kai; Zou, Shubing; Hu, Zhigang (Frontiers in Surgery, 2021)
Abstract Background: The aim of this study based on log odds of positive lymph nodes (LODDS) is to develope and validate an effective prognostic nomogram for patients with T3 and T4 gallbladder cancer (GBC) after resection. Patients and Methods: A total of 728 T3 and T4 gallbladder cancer patients after resection from the Surveillance, Epidemiology, and End Results (SEER) database, randomly divided into training cohort and validation cohort according to 7:3. Another 128 patients from The Second Affiliated Hospital of Nanchang University for external validation. The nomograms were built by the Cox regression model and the Fine and Grey’s model. Concordance index (C-index), calibration curve and the area under receiver operating characteristic (ROC) curve (AUC) were used to evaluate the nomogram and internal verification. The decision curve analysis (DCA) were used to measure the clinical applicability. Result: LODDS was independent prognostic predictor for overall survival(OS) and cancer-specific survival(CSS), and established the nomograms on this basis. The nomogram we have established has a good evaluation effect, with a C-index of 0.719(95%CI,0.707 to 0.731) for OS and 0.747(95%CI,0.733 to 0.760) for CSS. The calibration curve of OS and CSS both showed good calibration capability, and the AUC for predicting 1-,2- and 3-year 0.858,0.848 were and 0.811 for OS, and 0.794,0.793 and 0.750 for CSS. The DCA of nomograms both showed good clinical applicability. Conclusion: The nomogram can provide effective OS and CSS prediction for patients with advanced gallbladder cancer after surgery.